2022
DOI: 10.1088/2058-8585/ac5214
|View full text |Cite
|
Sign up to set email alerts
|

A review of silver nanowire-based composites for flexible electronic applications

Abstract: Silver nanowires (Ag NWs) have become a ubiquitous part of flexible electronic devices. The good electrical conductivity of silver, coupled with the excellent ductility and bendability exhibited by the wires make them ideal for flexible devices. Additionally, deposited films of Ag NWs are also found to be transparent due to the incomplete areal coverage of the wires. Thus, Ag NWs are widely used as transparent conducting electrodes (TCEs) for flexible and wearable electronics, replacing the traditionally used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 276 publications
1
45
0
Order By: Relevance
“…71 With these advances, AgNWs have been widely used to fabricate functional flexible/stretchable devices, such as electronic skin, solar cells, touch screens, and optoelectronic devices. 72–77…”
Section: Nano-conductive Materials For Stretchable and Flexible Elect...mentioning
confidence: 99%
See 1 more Smart Citation
“…71 With these advances, AgNWs have been widely used to fabricate functional flexible/stretchable devices, such as electronic skin, solar cells, touch screens, and optoelectronic devices. 72–77…”
Section: Nano-conductive Materials For Stretchable and Flexible Elect...mentioning
confidence: 99%
“…71 With these advances, AgNWs have been widely used to fabricate functional flexible/stretchable devices, such as electronic skin, solar cells, touch screens, and optoelectronic devices. [72][73][74][75][76][77] including surface science and surface engineering, transport and self-assembly of colloidal nanoparticles, and development of printing processes (e.g., inkjet printing, direct ink writing, electrohydrodynamic printing) for printed functional devices, such as stretchable electronics, magnetic devices, and medical devices.…”
Section: Agnwsmentioning
confidence: 99%
“…In order to solve these issues, they can be combined with polymers to manufacture nanocomposites with enhanced stretchability, superior mechanical strength, conductivity, and stability. Another approach is the combination with other nanoscale fillers like silver nanowires, that also display optimal properties for flexible electronic applications [ 65 ]. However, in order to use them in commercial applications, many challenges need to be addressed.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…In particular, CNT can form conductive bridges between the AgNWs, which enhance the conductivity. While the CNTs filled in the spaces between the nanowires, the AgNW formed a percolation current-carrying network, enabling local electron transport and lowering junction resistance [ 166 , 167 ]. Lee et al demonstrated the benefits of using both AgNW and CNT on a stretchable substrate and obtained a stretchability of over 460% [ 168 ].…”
Section: Applications Of Type and Chirality-separated Swcntmentioning
confidence: 99%